2008
DOI: 10.1111/j.1462-2920.2008.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes transcribed by Haemophilus parasuis in necrotic porcine lung through the selective capture of transcribed sequences (SCOTS)

Abstract: Haemophilus parasuis is the aetiological agent of Glässer's disease, which has received more attention in the past decade due to the increasing economic losses in the pig industry worldwide. Little is known about the mechanisms by which H. parasuis survives in the host. In this study, selective capture of transcribed sequences (SCOTS) was used to identify H. parasuis genes upregulated in necrotic porcine lung 7 days post infection. Thirty-eight genes were identified that were upregulated during infection of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…Based on gene sequence homology, a number of genes encoding putative sialic acid-related enzymes have been annotated in the genome of H. parasuis strain SH0165 (Xu et al, 2011). In addition, Jin et al (2008) reported the transcription of a siaB/neuA homologue during infection, suggesting a role for sialic acid in the pathogenesis of this bacterium. In this study, we analysed the presence of the genes nanH, siaB, neuA and lsgB in strains from different clinical origins and studied their association with virulence mechanisms already described for H. parasuis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on gene sequence homology, a number of genes encoding putative sialic acid-related enzymes have been annotated in the genome of H. parasuis strain SH0165 (Xu et al, 2011). In addition, Jin et al (2008) reported the transcription of a siaB/neuA homologue during infection, suggesting a role for sialic acid in the pathogenesis of this bacterium. In this study, we analysed the presence of the genes nanH, siaB, neuA and lsgB in strains from different clinical origins and studied their association with virulence mechanisms already described for H. parasuis.…”
Section: Introductionmentioning
confidence: 99%
“…O sorotipo 4 (39%) e os isolados não sorotipáveis (27%) foram os mais prevalentes nos rebanhos norte-americanos (OLIVEIRA et al, 2003) (KIELSTEIN & RAPP-GABRIELSON, 1992;NIELSEN, 1993). Outros estudos têm sido realizados para se comprovar a associação entre a expressão de fatores de patogenicidade e virulência em infecções por H. parasuis (JIN et al, 2008;DEL RÍO et al, 2006a;METCALF & MacINNES, 2007), embora nenhuma associação evidente com virulência pôde ser determinada. O desenvolvimento de ferramentas diagnósticas mais específicas, tais como a detecção de genes específicos para virulência, permitirá a identificação precisa de amostras virulentas.…”
Section: Sorotiposunclassified
“…As in other Gram-negative microorganisms, lipopolysaccharide, capsule, certain outer membrane proteins, fimbriae and neuraminidase have also been linked to the virulence of this bacterium (del Río et al 2005). Approximately 40 differentially expressed genes of this pathogen have been identified from infected pig lungs in our previous study (Jin et al 2008). However, the overall contribution of each component to the infection process remains unclear.…”
Section: Introductionmentioning
confidence: 99%